1998
DOI: 10.1021/ic971632y
|View full text |Cite
|
Sign up to set email alerts
|

(Pyrazolato)gold Complexes Showing Room-Temperature Columnar Mesophases. Synthesis, Properties, and Structural Characterization

Abstract: Mesogenic (pyrazolato)gold complexes of formula [Au(pz)]3 (pz = 3,5-bis(3‘,4‘-di-n-decyloxyphenyl)pyrazole (1), 3-(3‘,4‘,5‘-tri-n-decyloxyphenyl)-5-(3‘‘,4‘‘-di-n-decyloxyphenyl)pyrazole (2), 3-(2‘,3‘,4‘-tri-n-decyloxyphenyl)-5-(3‘‘,4‘‘,5‘‘-tri-n-decyloxyphenyl)pyrazole (3), 3,5-bis(3‘,4‘,5‘-tri-n-decyloxyphenyl)pyrazole (4)) have been prepared by reaction of the potassium salts of the nonmesogenic pyrazolate ligands with [AuCl(tht)] (tht = tetrahydrothiophene) in a 1:1 molar ratio. All these compounds show col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 34 publications
(30 reference statements)
2
63
1
3
Order By: Relevance
“…Indeed, gold(I) complexes of these ligands are trinuclear metallacycles [AuA C H T U N G T R E N N U N G (m-pz)] 3 that show thermodynamically stable columnar mesophases. [18,19] More recently, we have shown that the polycatenar pyrazolates are compatible with different coordination geometries and room-temperature mesophases have been described for coordination compounds with square-planar rhodium(I) or tetrahedral zinc(II); thus, these ligands are very useful for promoting columnar mesomorphism. [20,21] We describe herein a number of silver metallomesogens that exhibit columnar liquid-crystal phases and also report on the different and unexpected behavior compared to the analogous gold complexes.…”
Section: H T U N G T R E N N U N G Cycle [Ma C H T U N G T R E N N U mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, gold(I) complexes of these ligands are trinuclear metallacycles [AuA C H T U N G T R E N N U N G (m-pz)] 3 that show thermodynamically stable columnar mesophases. [18,19] More recently, we have shown that the polycatenar pyrazolates are compatible with different coordination geometries and room-temperature mesophases have been described for coordination compounds with square-planar rhodium(I) or tetrahedral zinc(II); thus, these ligands are very useful for promoting columnar mesomorphism. [20,21] We describe herein a number of silver metallomesogens that exhibit columnar liquid-crystal phases and also report on the different and unexpected behavior compared to the analogous gold complexes.…”
Section: H T U N G T R E N N U N G Cycle [Ma C H T U N G T R E N N U mentioning
confidence: 99%
“…A decrease in the clearing points was found on increasing the number of chains (Table 2), a finding consistent with the behavior observed in columnar liquid crystals that contain polycatenar pyrazolates, such as the analogous gold complexes. [19] However, the liquid-crystalline phases of the silver analogues are considerably more stable than those of the gold CTCs. ] n shows a co-A C H T U N G T R E N N U N G lumnar mesophase between room temperature and 143 8C.…”
Section: Armentioning
confidence: 99%
“…By considering the flat core of the anionic pyrazolato ligands, the approach of two Au I centers of molecules of the type [Au(pz R 2 )(PPh 3 )] (I) should be possible without considerable steric hindrance. Looking for molecular aggregations through Au ¥¥¥ Au contacts, we determined the crystal structure of a single crystal of [Au(pz R 2 )(PPh 3 )] 2 (R C 4 H 9 ÀOÀC 6 H 4 ; 1).…”
Section: Pyrazolatogold(i) Derivatives Of the Types [(Pph 3 )Au(màpz)mentioning
confidence: 99%
“…[7][8][9][10][11][12] 1H-Pyrazoles are structural building blocks that have the potential to self-organize into a rich variety of superstructures through hydrogen bonding. [13] As part of our research program, we have studied polycatenar 3,5-diaryl-1H-pyrazoles as promesogenic ligands in coordination compounds with boron, [14,15] gold, [16,17] zinc, [18] and rhodium [19] in order to obtain columnar mesophases. All of the complexes reported were liquid crystalline, despite the variety of shapes and geometries, with the mesophases obtained at room temperature in most cases.…”
Section: Introductionmentioning
confidence: 99%